AN ANALYSIS OF FIRST LANGUAGE ACQUISITION OF A THREE YEARS OLD CHILD: A CASE STUDY - Syarifah Hidayani (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
The process of acquiring language in a child occurs when the child is learning a mother tongue (native language). Language acquisition is the process of children getting the ability to capture, produce, and use words for understanding and communication.  In this case, the researcher presents how the child acquires the language. This research discusses the first language acquisition on a three-years child based on phonological, semantic and syntax aspects. This research will conduct with descriptive qualitative research. The objectives of descriptive qualitative study are obtained from the utterances of her boy named is Mu’ammar Syauqi Idris. The researcher also took the data by observation and video recording.  Based on the research, the researcher concluded that Mu’ammar able to communicate appropriately.